2018
DOI: 10.7150/thno.28676
|View full text |Cite
|
Sign up to set email alerts
|

Small Heterodimer Partner Regulates Circadian Cytochromes p450 and Drug-Induced Hepatotoxicity

Abstract: The role of small heterodimer partner (SHP) in regulation of xenobiotic detoxification remains elusive. Here, we uncover a critical role for SHP in circadian regulation of cytochromes P450 (CYPs) and drug-induced hepatotoxicity.Methods: The mRNA and protein levels of CYPs in the livers of wild-type and SHP-/- mice were measured by quantitative real-time polymerase chain reaction and Western blotting, respectively. Regulation of CYP by SHP was investigated using luciferase reporter, mobility shift, chromatin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 52 publications
6
49
0
Order By: Relevance
“…Our study showed that mice are sensitive to acetaminophen‐induced liver injury at night and that a change in Cyp2e1 activity was consistent with the sensitivity against acetaminophen‐induced liver injury (Figure ). These results are consistent with the findings of a previous report (Zhang et al, ). Acetaminophen is converted to NAPQI by Cyps (Cyp2e1, Cyp1a2 and Cyp3a), which then causes hepatotoxicity in mice.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study showed that mice are sensitive to acetaminophen‐induced liver injury at night and that a change in Cyp2e1 activity was consistent with the sensitivity against acetaminophen‐induced liver injury (Figure ). These results are consistent with the findings of a previous report (Zhang et al, ). Acetaminophen is converted to NAPQI by Cyps (Cyp2e1, Cyp1a2 and Cyp3a), which then causes hepatotoxicity in mice.…”
Section: Discussionsupporting
confidence: 94%
“…A (Figure c, d). Our results are consistent with those reported by other groups (Liu, Li, Xu, Xu, & Liu, ; Matsunaga et al, ; T. Zhang et al, ; Y.‐K. J. Zhang, Yeager, & Klaassen, ) and demonstrate that sensitivity to acetaminophen‐induced liver injury in mice is dependent on the time of administration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, REV‐ERBα/β play important roles in regulation of many other physiological processes including cell differentiation, inflammation, lipid, and glucose metabolism (Cho et al, ; Gibbs et al, ; J. Wang & Lazar, ). Our recent studies also suggest a critical role for REV‐ERBα in regulation of DMEs including CYP2B10 and carboxylesterases (Zhang et al, ; Zhao, Zhang, Yu, Guo, & Wu, ).…”
Section: Introductionmentioning
confidence: 73%
“…For instance, CYP2B10‐mediated detoxification of pentobarbital and cyclophosphamide is modulated by three clock output genes D‐site binding protein ( DBP ), hepatic leukaemia factor ( HLF ), and thyrotroph embryonic factor ( TEF ; Gachon, Olela, Schaad, Descombes, & Schibler, ). The circadian gene small heterodimer partner ( SHP ) participates in regulating toxicities of paracetamol, aflatoxin B1, and mitoxantrone (T. Zhang et al, ). Also, the two clock output genes HLF and E4BP4 control the diurnal rhythms of expression of the intestinal drug transporter P‐gp (ABCB1) and of digoxin accumulation (Murakami, Higashi, Matsunaga, Koyanagi, & Ohdo, ).…”
Section: Introductionmentioning
confidence: 99%